Pharmacokinetics and bioavailability of intravenous-to-oral enoxacin in elderly patients with complicated urinary tract infections. - Marchbanks, C R (1990)
The pharmacokinetics of oral fluoroquinolone antibiotics in normal volunteers have been studied extensively; however, limited patient data exist. Enoxacin steady-state pharmacokinetics and bioavailability were determined following repeated 400-mg intravenous (i.v.) and oral dosing by using compartmental and noncompartmental methods in 10 elderly (mean age, 73.8 years) men with complicated urinary tract infections. Average peak enoxacin concentrations following i.v. and oral dosing were 8.15 and 5.45 mg/liter, respectively. Mean values for major pharmacokinetic parameters (noncompartmental) were similar following i.v. and oral administration, respectively: area under the concentration-time curve from 0 to 12 h, 47.6 and 41.0 mg.h/liter; volume of distribution or volume of distribution/bioavailability, 1.61 and 1.99 liters/kg; total body clearance or total body clearance/bioavailability, 2.58 and 3.01 ml/min per kg; and half-life, 8.2 and 9.1 h. Parameters from analysis of enoxacin plasma concentration data by using a two-compartment pharmacokinetic model also revealed marked similarities between the two administration routes. Enoxacin was highly bioavailable (mean, 86.97%) following oral administration.